The Effect of On-Time Performance, Marketing Mix, and Service Excellence on Customer Satisfaction and Customer Loyalty - Widodo, Rintis Eko (Siber International Journal of Digital Business (SIJDB), 2025)
The purpose of this literature study is to develop a hypothesis regarding the influence between variables that can be used for further research in the field of marketing management. The literature review article on the influence of on-time performance, marketing mix, and service excellence on customer satisfaction and customer loyalty is a scientific article in marketing management. The approach used in this literature review is descriptive qualitative. The data collection technique is to use a literature study or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this study and is sourced from academic online media such as Thomson Reuters, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, each relevant previous article was used to review each independent variable. The results of this literature review article are: 1) On-time performance affects customer satisfaction; 2) Marketing mix affects customer satisfaction; 3) Service excellence affects customer satisfaction; 4) On-time performance affects customer loyalty; 5) Marketing mix affects customer loyalty; 6) Service excellence affects customer loyalty; and 7) Customer satisfaction affects customer loyalty.